If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 6 + 9(x + -6) Reorder the terms: 15 = 6 + 9(-6 + x) 15 = 6 + (-6 * 9 + x * 9) 15 = 6 + (-54 + 9x) Combine like terms: 6 + -54 = -48 15 = -48 + 9x Solving 15 = -48 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 15 + -9x = -48 + 9x + -9x Combine like terms: 9x + -9x = 0 15 + -9x = -48 + 0 15 + -9x = -48 Add '-15' to each side of the equation. 15 + -15 + -9x = -48 + -15 Combine like terms: 15 + -15 = 0 0 + -9x = -48 + -15 -9x = -48 + -15 Combine like terms: -48 + -15 = -63 -9x = -63 Divide each side by '-9'. x = 7 Simplifying x = 7
| (5x)=(3x+18) | | 2(x+2)=18 | | 5x=(x+18) | | x^4-9x^3+21x^2-x-30=0 | | x^4-9x^3-21x^2-x-30=0 | | 32=0.66x-34 | | x^3-4x^2-3x+12=0 | | 9(2x-8)=3(6x+9) | | 15=9-6x | | (4y)+(3y)=180 | | .5x=1.45 | | (3x-18)+(2x+12)=180 | | 2(2)+4=2x | | 3a-3(7+5a)=9(2+a) | | (4y)+(3x-18)+(3z)+(2x+12)=360 | | 2(2)+4=x | | 12x-25=6x+15 | | (19x-17)-(3x-72)= | | 8(120)=x | | 8(15)=y | | 7+2t-4=8t+11-5t | | 2x-15=5x | | 6x+2=4x+12 | | 4x+63=14x-7 | | -3(x+5)=-27 | | 9x+17=5x+13 | | 6(2x+3)=66 | | 3(m-4)+2(5+2m)=29 | | 5+7y=2x+7+6y | | 16x+12=8x+41 | | 6x=3x+3 | | 9x+6=-57 |